Thermosensitive hydrogel containing chinese herbal compound extract and hyaluronic acid-chitosan quaternary ammonium salt microspheres for topical application: preparation and characterization - Li, Peiyang; Zhao, Jianhao; Wang, Junlin; Nie, Hong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Allergic contact dermatitis (ACD) is a highly prevalent allergic inflammatory dermatosis with persistent severe pruritus. Zhi-Yang-Fang (ZYF), a topical Chinese herbal compound used in clinical practice for treating ACD, has certain drawbacks such as inconvenience in use and its impact on aesthetics. This research aimed to overcome these shortcomings by developing an F127/F68-based thermosensitive hydrogel containing ZYF aqueous extract and hyaluronic acid-chitosan quaternary ammonium salt (HA-HTCC) microspheres. The 19 major components of ZYF aqueous extract were preliminarily identified using ultra-high-performance liquid chromatography coupled to Quadrupole-Exactive Orbitrap mass spectrometry (UPLC-Q Exactive Orbitrap-MS) analysis. HA-HTCC microspheres and HA-HTCC microspheres containing ZYF aqueous extract were prepared using the physical cross-linking method, and the success of the preparation was confirmed through a series of characterisations. The concentration of F127 and F68 was screened. The proportions of each substance in the final hydrogel formulation were determined, prepared using the cold method, and characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and a rotational rheometer. These technologies verified the successful preparation, temperature sensitivity, and stability of the hydrogel. The hydrogel developed may be considered a promising approach for the management of ACD.